The Politics of War : Race, Class, and Conflict in Revolutionary Virginia - McDonnell, Michael A. (Book collections on Project MUSE., 2007)
"War often unites a society behind a common cause, but the notion of diverse populations all rallying together to fight on the same side disguises the complex social forces that come into play in the midst of perceived unity. Michael A. McDonnell uses the Revolution in Virginia to examine the political and social struggles of a revolutionary society at war with itself as much as with Great Britain. McDonnell documents the numerous contests within Virginia over mobilizing for war--struggles between ordinary Virginians and patriot leaders, between the lower and middle classes, and between blacks and whites. From these conflicts emerged a republican polity rife with racial and class tensions. Looking at the Revolution in Virginia from the bottom up, The Politics of War demonstrates how contests over waging war in turn shaped society and the emerging new political settlement. With its insights into the mobilization of popular support, the exposure of social rifts, and the inversion of power relations, McDonnell's analysis is relevant to any society at war."--Publisher's description